Implementation of Analytic Hierarchy Process Method for Selection of Supplier of Flour Raw Materials in CV. Gangsar in Tulungagung - Indri Wijayanti; Elia Ardyan (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study also aims to determine suppliers who have the best performance in providing raw material supplies according to analysis and calculations using the Analytical Hierarchy Process method for CV. Gangsar. Design/methodology/approach: The type of research used in this research is quantitative with the Multi-Criteria Decision Making (MCDM) method, more specifically the Analytic Hierarchy Process method. This research is located in CV. Gangsar which is located on Jl. Demuk No. 37 Ngunut Village, Ngunut District, Tulungagung Regency, East Java. Sampling in this study used a non-probability sampling method with a purposive sampling technique. Data analysis technique using AHP. Findings: The results of the study indicate the criteria that can be considered to choose the best flour supplier for CV. Gangsar is price, quality, delivery accuracy, quantity accuracy, and customer care. Quality is the most important criterion with a weight of 0.326, then the price criteria with a weight of 0.289, then the criteria for accuracy of delivery with a weight of 0.171, then the criteria for accuracy of quantities with a weight of 0.140, and the last criterion of customer care with a weight of 0.074. Which flour supplier is the most appropriate to support the production performance of CV. Gangsar can be seen from the greatest weight. The highest weight is Indotapioka with a value of 0.378, followed by Sari Bumi with a weight of 0.330, and finally Sungai Budi with a weight of 0.292. Therefore, Indotapioka Jaya is the most appropriate company to support the production performance of CV. Gangsar. The company should use the research results as input when choosing the right supplier. Paper type: Research paper